Mutation of the Na+-K+-2Cl− cotransporter NKCC2 in mice is associated with severe polyuria and a urea-selective concentrating defect without hyperreninemia - Kemter, Elisabeth Gabriele; Rathkolb, Birgit; Bankir, Lise; Schrewe, Anja; Hans, Wolfgang; Landbrecht, Christina; Klaften, Matthias; Ivandic, Boris; Fuchs, Helmut; Gailus-Durner, Valérie; Hrabé de Angelis, Martin; Wolf, Eckhard; et al. (American journal of physiology. Renal physiology, 2010)
The bumetanide-sensitive Na+-K+-2Cl− cotransporter NKCC2, located in the thick ascending limb of Henle's loop, plays a critical role in the kidney's ability to concentrate urine. In humans, loss-of-function mutations of the solute carrier family 12 member 1 gene (SLC12A1), coding for NKCC2, cause type I Bartter syndrome, which is characterized by prenatal onset of a severe polyuria, salt-wasting tubulopathy, and hyperreninemia. In this study, we describe a novel chemically induced, recessive mutant mouse line termed Slc12a1I299F exhibiting late-onset manifestation of type I Bartter syndrome. Homozygous mutant mice are viable and exhibit severe polyuria, metabolic alkalosis, marked increase in plasma urea but close to normal creatininemia, hypermagnesemia, hyperprostaglandinuria, hypotension,, and osteopenia. Fractional excretion of urea is markedly decreased. In addition, calcium and magnesium excretions are more than doubled compared with wild-type mice, while uric acid excretion is twofold lower. In contrast to hyperreninemia present in human disease, plasma renin concentration in homozygotes is not increased. The polyuria observed in homozygotes may be due to the combination of two additive factors, a decrease in activity of mutant NKCC2 and an increase in medullary blood flow, due to prostaglandin-induced vasodilation, that impairs countercurrent exchange of urea in the medulla. In conclusion, this novel viable mouse line with a missense Slc12a1 mutation exhibits most of the features of type I Bartter syndrome and may represent a new model for the study of this human disease.
Im Titel erscheinen die Zeichen - und + stets hochgestellt
Gesehen am 08.03.2023